Effect of foliar spraying with algae suspension on leaf and fruit quality parameters of apple varieties - Ambrus, A.; Nyéki, J.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2012)
Foliar nutrition experiment was made to investigate the effect of algae products on fruit quality of apples (Malus domestica Borkh.). The study was conducted in 2011 at Siófok inWest-Hungary on cv. ‘Jonagored’ and ‘Idared’grafted on M9 rootstock. In our trial leaf diagnostic and fruit quality measurements were made to study the effectiveness of applied products. Relative leaf chlorophyll content was determined by a portable chlorophyll meter. Fruit weight and shape index were measured. Fruit inner qualifying parameters like titratable acid content and Brix value were also determined. It can be stated that the used products had traceable effect on investigated fruit parameters. Although, leaf N content was not effected by treatments significantly, relative leaf chlorophyll content significantly increased by both treatments. Used products significantly increased the fruit weight and shape index. Applied treatments significantly decreased the pH of pulp. Treatments increased the acid contents (fumaric, citric, malic) of apples and decreased the amount of monosaccharides. It means that the applied treatments pushed out the ratio of acid/sugar.